Utilization of Interspecific High-Density Genetic Map of RIL Population for the QTL Detection and Candidate Gene Mining for 100-Seed Weight in Soybean - Karikari, Benjamin; Chen, Shixuan; Xiao, Yuntao; Chang, Fangguo; Zhou, Yilan; Kong, Jiejie; Bhat, Javaid Akhter; Zhao, Tuanjie (Frontiers in Plant Science, 2019)
Seed-weight is one of the most important traits determining the soybean yield. Hence, it is prerequisite to have detailed understanding of the genetic basis regulating seed-weight for the development of improved cultivars. In this regard, the present study has used high-density interspecific linkage map of NJIR4P recombinant inbred population (RIL) evaluated in four different environments to detect stable QTLs as well as mine candidate genes for 100-seed weight. In total, 19 QTLs distributed on 12 chromosomes were identified in all individual environments plus combined environment, out of which seven were novel and eight are stable identified in more than one environments. However, all the novel QTLs were minor (R2<10%). The remaining twelve QTLs detected in this study were co-localized with the earlier reported QTLs, with narrow genomic regions, and out of these, only two QTLs were major (R2>10%) viz., qSW-17-1 and qSW-17-4., both of them were previously reported on Chr17. Moreover, 12 earlier reported QTLs validated by the present study were identified in the narrow genomic regions. Beneficial alleles of all identified QTLs were derived from cultivated soybean parent (Nannong493-1). Based on the PANTHER analysis, gene annotation information and literature search, 2931 genes within five stable QTLs were predicted to be possible candidate genes that might regulate seed-weight/size in soybean. However, it needs further validation to confirm their role in seed development. In conclusion, the present study provides better understanding of trait genetics and candidate gene information through the use high-density inter-specific bin map, and also revealed considerable scope for genetic improvement of 100-seed weight in soybean using marker-assisted breeding (MAB).